In vitro efficacy of sodium selenite in reducing toxin production, spore outgrowth and antibiotic resistance in hypervirulent Clostridium difficile. Issue 7 (7th June 2019) - Pellissery, Abraham Joseph; Vinayamohan, Poonam Gopika; Yin, Hsin-Bai; Mooyottu, Shankumar; Venkitanarayanan, Kumar
Abstract : Purpose. This study investigated the efficacy of the essential mineral, selenium (sodium selenite), in reducing the toxin production, spore outgrowth and antibiotic resistance of Clostridium difficile in vitro . Methodology. Two hypervirulent C. difficile isolates were cultured in brain heart infusion broth with and without a sub-minimum inhibitory concentration (sub-MIC) of sodium selenite, and the supernatant and bacterial pellet were harvested for total toxin quantitation and RT-qPCR analysis of toxin-encoding genes, respectively. Additionally, C. difficile isolates were cultured in brain heart infusion broth containing 0.5 or 1× the minimum inhibitory concentration (MIC) of either ciprofloxacin or vancomycin with or without sub-MICs of sodium selenite. Further, the effect of sodium selenite on C. difficile germination and spore outgrowth was also determined by exposing C. difficile spores to a sub-MIC of sodium selenite in a germination medium and measuring the germination and outgrowth by measuring the optical density at 600 nm. Results. Sodium selenite significantly reduced C. difficile toxin synthesis, cytotoxicity and spore outgrowth. Further, the expression of the toxin production genes, tcdA and tcdB, was downregulated in the presence of sodium selenite, while sodium selenite significantly increased the sensitivity of C. difficile to ciprofloxacin, but not vancomycin, as revealed by decreased bacterial growth in samples containing ciprofloxacin+selenium compared to the antibiotic control. Although the sub-MIC of sodium selenite did not inhibit spore germination, it was capable of completely inhibiting spore outgrowth. Conclusion. Our results suggest that sodium selenite could potentially be used to control C. difficile and indicate that future in vivo studies are warranted.